Intellectual capital as a source of an economy based on knowledge at the stage of post-industrial society (The Journal of Psychology and Sociology, 2013)
The paper analyzes the theory of intellectual resources, intellectual capital in terms of innovative development of an economy based on knowledge. Modern societies have embarked on the formation of their economies and social development with a focus on knowledge, in this regard, the knowledge economy is seen as a transition to the next economy, a new stage of its development, which is based on science and innovation. Intellectual capital and human capital are considered as sources of post-industrial development. The relevance of the theory of intellectual capital in the modernization of Kazakhstan society reveals.
Keywords: post-industrial society; knowledge economy; Kazakhstan; modernization and innovative development; intellectual capital.